1996
DOI: 10.1021/es960269b
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of PAHs in the U.K. Atmosphere Using Pine Needles

Abstract: A study of the spatial distribution and mixture of polycyclic aromatic hydrocarbons (PAHs) in pine needles sampled across the U.K. in the summer of 1994 is presented. PAHs reach pine needles via atmospheric transport and deposition processes. Phenanthrene was distributed irregularly across the U.K., while the other PAHs generally decreased on a northward gradient from the southern England to northern Scotland by a factor of ∼7. A relationship was found between the mean PAH concentrations of each area sampled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(78 citation statements)
references
References 38 publications
10
66
0
2
Order By: Relevance
“…(2010a) and Amigo et al (2011) observed that the urban and industrial sites have the predominant mean PAH incidence, followed by the rural sites and with the remote sites showing clearly the lowest levels. Similar features were also mentioned in other parts of the world (Tremolada et al 1996;Lang et al 2000;Piccardo et al 2005;Tian et al 2008). …”
Section: Comparison For Vegetation Levelssupporting
confidence: 76%
“…(2010a) and Amigo et al (2011) observed that the urban and industrial sites have the predominant mean PAH incidence, followed by the rural sites and with the remote sites showing clearly the lowest levels. Similar features were also mentioned in other parts of the world (Tremolada et al 1996;Lang et al 2000;Piccardo et al 2005;Tian et al 2008). …”
Section: Comparison For Vegetation Levelssupporting
confidence: 76%
“…Compared with the reports published in other urban region, the result was significantly lower than those presented in urban soil fiom New Orleans , 1999) and Tianjin City of China (0.818 kg/g as mean ;Wang et al, 2003). It was reported that PAHs in soils from urban areas were approximately 2-10 higher than those in rural areas (Lodovici et al, 1994;Tremolada et al, 1996;Wagrowski and Hitcs, 1997). Here, the mean of C 16 EPA-PAHs (1.637 kg/g) was nearly 4 times higher than that in the rural area (0.464 kg/g; Ma et al, 2005) and was much higher than those from the exurb of Beijing (0.058-0.141 pg/g; Ge et al, 2004).…”
Section: Pahs Determinationmentioning
confidence: 66%
“…They can grow up to several years old, depending on the species and the environmental conditions. Therefore, it has been demonstrated that pine needles contain complementary monitoring information, such as a trustworthy time-integrated pollution dataset able to produce a comprehensive assessment of levels, sources and spatio-temporal patterns of PAHs Lehndorff and Schwark, 2009a;Lehndorff and Schwark, 2009b;Navarro-Ortega et al, 2012;Noth et al, 2013;Ratola et al, 2010b;Tremolada et al, 1996). There are major difficulties in obtaining accurate estimations of the origin of the PAHs, due to the complex mixtures of individual PAHs released to the environment from different sources of emission that may be localized within a specific geographical area.…”
Section: Introductionmentioning
confidence: 99%